2014
DOI: 10.1111/1462-2920.12480
|View full text |Cite
|
Sign up to set email alerts
|

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from Lake Yuehu in China

Abstract: Two morphotypes of multicellular magnetotactic prokaryotes (MMPs) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet-shaped magnetite magnetosomes alone, or both bullet-shaped magnetite and rectangular greigite magnetosomes. They showed north-seeking magnetotaxis, pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(114 citation statements)
references
References 45 publications
3
111
0
Order By: Relevance
“…By electron microscopy the cells of an MMP appear to be connected by tight intercellular junctions similar to animal epithelia [33], and dislodgement of any individual cells leads to loss of motility, suggesting these organisms can only function as a multicellular unit [30]. MMPs have been observed to reproduce by fission of the whole organism without going through a unicellular state [23,24,28], making it the only known example of a bacterium without a unicellular phase in its lifecycle. Many fundamental aspects of MMP biology remain to be determined, including what mediates cell-cell attachment, what types of intercellular signaling is used to coordinate movement, and how reproduction is orchestrated.…”
Section: Classes Of Multicellular Bacteriamentioning
confidence: 99%
“…By electron microscopy the cells of an MMP appear to be connected by tight intercellular junctions similar to animal epithelia [33], and dislodgement of any individual cells leads to loss of motility, suggesting these organisms can only function as a multicellular unit [30]. MMPs have been observed to reproduce by fission of the whole organism without going through a unicellular state [23,24,28], making it the only known example of a bacterium without a unicellular phase in its lifecycle. Many fundamental aspects of MMP biology remain to be determined, including what mediates cell-cell attachment, what types of intercellular signaling is used to coordinate movement, and how reproduction is orchestrated.…”
Section: Classes Of Multicellular Bacteriamentioning
confidence: 99%
“…BW-1 represents just one of the two known greigite-producing MTB morphotypes and has never been characterized by any of the magnetofossil detection method in use today. There is also a lack of magnetic characterization on similar but uncultivated greigite-producing MTB large rods, as well as the other known greigite-producing MTB, multicellular magnetotactic prokaryote, all of which commonly produce disaggregated magnetosome clusters and bundles 3,4,[30][31][32][33][34] . Non-chain magnetosome geometry is not restricted to greigite-producing MTB, as there have been numerous reports of uncultivated magnetite-producing MTB that do not form simple single chains 35 and whose magnetic properties remain largely unknown.…”
mentioning
confidence: 99%
“…At low magnetic fields, such as the Earth's, they swim in complex, looping trajectories nearby the obstacle. Chemotaxis was observed in a single MMP species (Wenter et al, 2009), whereas photophobic responses have been reported in both spherical and ellipsoidal MMPs (Shapiro et al, 2011;Zhou et al, 2012;Chen et al, 2015;Zhang et al, 2014), including 'Ca. Translational velocities in spherical MMPs, including 'Ca.…”
Section: Introductionmentioning
confidence: 98%
“…These are attached to cytoskeletal fibres allowing the interaction of their magnetic dipole moment with the local field to generate a torque that aligns the whole microorganism along the magnetic field lines while it swims propelled by flagella (Faivre and Schuler, 2008). Magnetotaxis has also been shown to be coupled to chemotaxis (Wenter et al, 2009) and phototaxis (Frankel et al, 1997;Chen et al, 2011;Shapiro et al, 2011;Zhou et al, 2012;Almeida et al, 2013;Azevedo et al, 2013;Zhou et al, 2013;Chen et al, 2015;Zhang et al, 2014;De Melo and Acosta-Avalos, 2017). In several cultivated unicellular magnetotactic bacteria, magnetotaxis is coupled to aerotaxis, in a behaviour described as magneto-aerotaxis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation